An Efficient Connected-Component Labeling Algorithm for 3-D Binary Images - Zhao, Xiao; Chao, Yuyan; Zhang, Hui; Yao, Bin; He, Lifeng (IEEE Open Journal of the Computer Society, 2023)
Conventional voxel-based algorithms for labeling connected components in 3D binary images use the same mask to process all object voxels. To reduce the number of times that neighboring voxels are checked when object voxels are processed, we propose an algorithm that uses two different masks for processing two different types of object voxels. One type of mask is used when the voxel preceding the object voxel being processed is an object voxel, and the other type is used otherwise. In either case, an optimal order is used for checking the voxels in the corresponding mask. Experimental results demonstrate that our proposed algorithm checked fewer voxels, and was more efficient than conventional algorithms.